Rural Development Multifunctionality – The Example of Sheep Breeding in Southern Poland - Kamila MUSIAL (Communications of International Proceedings, 2023)
Sheep production in Poland for many years has been facing continuous recession, however its role can be considered in various aspects. Interesting way to describe this broad phenomenon may be a method proposed by Van Huylenbroeck, that is extrapolated from widely understood agriculture. According to that system individual functions were assigned to different colors: white, yellow, green and blue, relatively to the roles they perform. On this basis, functions specified as 'white', correspond to the matter of ensuring food security and diversity, by maintaining its high quality and variety, in terms of assortment. The aim of the 'yellow' function is to support the coherence of rural areas, for example by maintaining jobs in agriculture, through the development of production and services directly linked to sheep grazing. At present, encouragement for keeping these animals may be also possibility of receiving different EU subsidies under the Common Agricultural Policy. Furthermore, there are also included functions, which contribute to the cultural grazing of sheep in the area of the Polish Carpathians, that in turn guarantee maintaining the tradition of folk culture. Moreover, 'green' functions include shaping and preserving of cultural landscape that can be sustained by sheep grazing as well as sustaining high biodiversity, and 'blue' functions are related to the water resources and its quality.
Keywords: multifunctionality of sheep breeding; rural areas; productive and non-productive role; cultural grazing; the Polish Carpathians